Stimulation through Play for Children with Special Needs: Array - Susanu, Neaga (New Trends in Psychology, 2021)
The world unfolds progressively in front of the child, through sensory and motor experiences. At this stage of development the child can often be vulnerable. A child with special needs may not be as eager to try new experiences or stimuli as a regular child. He may not even play and, without stimulation, his condition does not improve through daily experiences. When a child's development is delayed or slowed down due to deficiencies or an abnormal environment, the first years of life are not enough for a child to become aware of his body or to feel safe with or without other people - for example, to start to develop their autonomy.